2017
DOI: 10.22616/rrd.23.2017.049
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilizer influence on winter wheat yield and yield components depending on soil tillage and forecrop

Abstract: Wheat (Triticum aestivum) is one of the main crops grown in Latvia. Nitrogen fertilizer is one of the most important factors affecting the acquired yield and its quality. The aim of this paper is to describe the nitrogen fertilization impact on winter wheat yield and yield components under two soil tillage systems and after two forecrops. Field trials were carried out at Research and Study farm 'Peterlauki' of Latvia University of Agriculture (56° 30.658°C N and 23° 41.580°C E) in 2014/2015 and 2015/2016. Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 8 publications
5
21
0
2
Order By: Relevance
“…In addition, nitrogen stimulates the plant to consume other activating elements, thus improving growth measures and all yield components and grain yields per unit area. Such reports are in clear compliance with those of Kandil et al (2016), Litke et al (2017), Mosanaei et al (2017), Seadh et al (2017), Belete et al (2018), Imdad Ullah et al (2018 and Liu et al (2019).…”
Section: Effect Of Nitrogen Fertilizer Levelssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, nitrogen stimulates the plant to consume other activating elements, thus improving growth measures and all yield components and grain yields per unit area. Such reports are in clear compliance with those of Kandil et al (2016), Litke et al (2017), Mosanaei et al (2017), Seadh et al (2017), Belete et al (2018), Imdad Ullah et al (2018 and Liu et al (2019).…”
Section: Effect Of Nitrogen Fertilizer Levelssupporting
confidence: 86%
“…All plant biochemical processes are regulated primarily by nitrogen and its associated compounds, which are important for wheat growth and development. (Kandil et al, 2016 ;Litke et al, 2017 ;Mosanaei et al, 2017 ;Seadh et al, 2017 ;Belete et al, 2018 ;Imdad Ullah et al, 2018 andLiu et al, 2019). Therefore, one of the beneficial factors for growing wheat growth and productivity is the need to apply the required amount of nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors claim that non-inversion tillage has no effect on the yield of cereals [11,[43][44][45][46]. Others have shown decreased cereal yield under no-ploughing conditions [47][48][49][50]. Some studies have found an increase in cereal yield in reduced and no-tillage soil tillage systems [40,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the study of Ruža et al (2012) on the effect of N-fertilization rate showed that the grain yield of winter wheat increased until the rate of 120-150 kg N/ha, but the grain quality increased until the rate of 180 kg N/ha. Litke et al (2017) showed that grain yield of winter wheat significantly increased until the nitrogen fertilizer rate of 180 kg N/ha after both forecrops (winter wheat and winter rape). For economic and ecological reasons, excessive fertilizer N-input to cropping systems is critical.…”
Section: Discussionmentioning
confidence: 99%